2015
DOI: 10.1002/mds.26147
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of Parkinson's disease among Navajo people living in the Navajo nation

Abstract: Parkinson's disease (PD) is largely unstudied among American Indians. Unique populations might harbor clues to elusive causes. We describe the incidence and prevalence of PD among Navajo people residing in the Navajo Nation, home to the largest American Indian tribe in the United States. We analyzed 2001-2011 inpatient and outpatient visit data for Navajo people obtained from the Indian Health Service, which provides health care to American Indian people living on the Navajo Reservation. Cases were defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
6
2
Order By: Relevance
“…Our study showed a moderate but significant increase in PD incidence in Taiwan, which is inconsistent with the reports from previous studies that presented a stable [ 4 , 5 , 7 , 9 , 10 ] or decreasing trend [ 8 , 22 ]. Studies conducted in Japan (1992 and 2004) [ 5 ], Argentina (2003 and 2008) [ 9 ], Indian Navajo Nation of the US (2002–2004 and 2009–2011) [ 10 ], and France (2005 and 2010) [ 7 ] all demonstrated relatively stable PD incidences. A decreasing trend in incidence of PD was observed in a UK study reporting an average reduction by 6% annually from 1999 to 2009 [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study showed a moderate but significant increase in PD incidence in Taiwan, which is inconsistent with the reports from previous studies that presented a stable [ 4 , 5 , 7 , 9 , 10 ] or decreasing trend [ 8 , 22 ]. Studies conducted in Japan (1992 and 2004) [ 5 ], Argentina (2003 and 2008) [ 9 ], Indian Navajo Nation of the US (2002–2004 and 2009–2011) [ 10 ], and France (2005 and 2010) [ 7 ] all demonstrated relatively stable PD incidences. A decreasing trend in incidence of PD was observed in a UK study reporting an average reduction by 6% annually from 1999 to 2009 [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies reported that the prevalence of PD had increased over the past decades, partially attributed to the increasing older population worldwide [ 3 8 ]. By contrast, most studies showed no substantial changes in the incidence of PD over time [ 4 , 5 , 7 , 9 , 10 ]. Moreover, race/ethnic variations in PD incidence and prevalence have been reported [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this population‐based study of diabetic patients, we observed a higher risk of PD in female relative to male subjects. In general population studies, PD incidence is a little higher in males, but in diabetic populations, females have higher risk of PD; the mechanisms are not still known. The possible mechanisms may be related to estrogen effects on dopaminergic neurons and pathways in the brain .…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, this is the first epidemiologic study of HD in an American Indian tribe and the only report detailing the absence of HD in any population. Taken with studies of amyotrophic lateral sclerosis 3 and Parkinson disease, 4 these data point to differentially distributed neurodegenerative disorders among American Indians and other populations. Research into the reasons underlying these contrasts could yield better understanding of often cryptogenic and universally incurable brain disorders.…”
mentioning
confidence: 67%
“…Methods. The e-Methods on the Neurology ® Web site at Neurology.org and previous articles by this group 3,4 describe the methodology in detail. We sought to determine average annual incidence and point prevalence rates of HD among Navajo residents of the Navajo Nation during 2001-2011.…”
mentioning
confidence: 99%